Pengaruh Kompensasi terhadap Kualitas Pelayanan Publik pada Pemerintahan Kecamatan Ratahan Kabupaten Minahasa Tenggara - Langingi, Elza; PANGKEY, MASJE; LONDA, VERY (JURNAL ADMINISTRASI PUBLIK, 2018)
This research is dilator by the problems that exist in Ratahan District Government of South Minahasa Regency thatis in Effect of Compensation to Quality of Public Service which still has not give contribution optimally. The existence of factorsthat affect the compensation, among others, employee performance and employee job satisfaction. In doing a job, employeesshould have high performance. Therefore it is necessary to have a good compensation effect in order to improve the performanceof the employees.Compensation is an important factor affecting how and why people work in an organization, so that employees can work fulltime to achieve the optimum level of organizational success. Quality of Public Service is the ability of public service officers toprovide a sense of satisfaction in meeting the needs of the community very well so as to provide a good perception by thecommunity itself. The purpose of this study is to determine whether there is effect of compensation on the quality of publicservices in the Government of Ratahan District South Minahasa Regency.In this research the method used is quantitative method. While the data analysis technique used is a correlation analysis andsimple linear regression analysis to show how far the relationship between the two variables. Based on the results of researchconducted and continued by analyzing the data obtained, then the result is that there is a strong relationship between the effectof compensation on public service quality of 0.624. This means that hypothesis testing is accepted. From the research resultsobtained coefficient of determination of 38.93%, the remaining 61.07% influenced from other factors that are not included inthis study.Keywords: Effect of Compensation, Quality of Public Service